Pengaruh Penggunaan Metode Show And Tell Terhadap Kemampuan Berbicara Anak Usia 5-6 Tahun Di RA Al Anshori - Fauziyyah, Nida Fauziyyah; Samin Syahidin (Kiddie: Early Childhood Education and Care Journal, 2023)
In essence, the ability to speak in early childhood is an important skill for communication, learning, and social interaction. This helps in the development of language, cognitive, self-expression, as well as being the basis for reading and writing. The aim of this study was to determine the effect of the show and tell method on the speaking ability of children aged 5-6 years. This research method uses a quasi-experimental design quantitative approach. Types of data are grouped into 2, namely primary and secondary. The population in this study were children aged 5-6 years who attended school in Raudhatul, Tegal Munjul Village, Purwakarta District. Then the samples taken were 30 children, namely 15 children in the experimental class and 15 children in the control class. Data analysis techniques use SPSS Type 25.0. . Based on the results of calculations using SPSS type 25.0 through an independent t test, the value of the t test t count is 6.339 with df = 28. Price t table = with a significant value (P) = 0.000 > Î± = 0.05. Thus the calculated t value > t table which means H0 is rejected and H1 is accepted. And it can also be seen that the value of sig (2 tailed) = 0.000 <0.05, which means that the value of sig (2) is less than 0.05, then H0 is rejected and H1 is accepted. Thus, the value of t count > t table means Ho is accepted Â and H1 is rejected. So, the value of t count > t table, which means that Ho is rejected and Ha is accepted. So it can be concluded that the show and tell method has a significant influence on children's speaking abilities.